Our experience in digital reimplantation and distant functional results - Fossati, Enrique; Irigaray, Alberto; Roncagliolo, Aldo; Asurey, Néstor (Cirugía del Uruguay, 1986)
Success in digital reimplantatlons requires adequate operativa indication, a correctiy trained staff of surgeons and appropiate surgical instruments. Microsurgery techniques empioyed include not only vascular sutures but also suture of the nerves and tendlnosuture which allow mor successful resuils than !hose attained by conventional techniques. In a four years' period, 61 fingers and 2 hands have been reimplantad having achieved a success average of 86%. Later results in the restoration of the function are presentad, evaluating same by various procedures.